Between Human Rights and Justice Principle in Children’s Civil Rights - Novenanty, Wurianalya Maria (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2016)
Children’s rights are fundamental in a country. Children are the future generation of a country. They have rights in civil law field. The examples of such rights are the right to have family name, the right to get alimony, and the right to get inheritance from the parents. Indonesian Law Number 1 of 1974 regarding Marriage (Marriage Law) distinguishes the civil rights of legitimate and illegitimate children. In 2010, the Indonesian Constitutional Court produced a decision which became a controversial decision because it was deemed to ‘legalize’ illegitimate child to have the same rights as legitimate child. The reason behind such decision is the human rights which should apply nondiscriminative principle. Some parties disagree with the reasoning behind this decision. They consider the decision unjust and that it violates social and religious norms in giving illegitimate and legitimate children the same rights in spite of the status difference. The author will discuss children’s civil rights based on civil law, human rights, and justice principle in Indonesia.